1996
DOI: 10.1203/00006450-199605000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Management of Late Anemia in Rhesus Hemolytic Disease: Use of Recombinant Human Erythropoietin (A Pilot Study)

Abstract: The management of (Rhesus) hemolytic disease of the fetus and newborn includes intrauterine transfusions to prevent the development of hydrops, treatment of the possible hyperbilirubinemia in the immediate postnatal period, and treatment of late anemia. Low levels of serum erythropoietin due to suppression of the bone marrow by multiple intrauterine transfusions is a suggested mechanism for this anemia. The aim of our study was to test whether recombinant human erythropoietin reduced the need for erythrocyte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…The possible explanations of anemia are intramedullary destruction of normoblasts with Rh antibodies and low erythropoietin levels due to suppression of the bone marrow by IUT [1,6,9]. These patients require erythrocyte transfusions in the postnatal period, and the use of rHuEPO may reduce the need for postnatal transfusions [10][11][12][13]. Even though rHuEPO administration is highly effective in many patients, treatment of hyporegenerative anemia with rHuEPO may be ineffective when anti-D titers are high [14].…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations of anemia are intramedullary destruction of normoblasts with Rh antibodies and low erythropoietin levels due to suppression of the bone marrow by IUT [1,6,9]. These patients require erythrocyte transfusions in the postnatal period, and the use of rHuEPO may reduce the need for postnatal transfusions [10][11][12][13]. Even though rHuEPO administration is highly effective in many patients, treatment of hyporegenerative anemia with rHuEPO may be ineffective when anti-D titers are high [14].…”
Section: Discussionmentioning
confidence: 99%
“…Ohls et al [5] started EPO treatment at day 85 of life, but some authors started earlier (first or second week of life) [31]. On the other hand, Ovali et al [7] suggested that EPO treatment could be individualized because some patients develop anemia earlier than others.…”
Section: Discussionmentioning
confidence: 99%
“…Ohls et al [5] were the first to report the use of EPO in vivo as treatment for the late hyporegenerative anemia of Rh hemolytic disease in 2 patients. Ulteriorly, three more studies [3,6,7] described the use of EPO therapy. Only one of these studies was controlled [7], including 20 newborns (10 in each group), and showed that the treatment decreased the need for erythrocyte transfusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depuis, bien d'autres bénéfices ont été mis en avant : l'aspect thérapeutique dans les incompatibilités maternofoetales [1], mais aussi récemment l'aspect neuroprotecteur dans le cadre des anoxo-ischémies périnatales [2].…”
Section: Introductionunclassified